Efektivitas Penggunaan Speech Trainer Pada Kasus Gangguan Pendengaran Studi Kasus Di YPAC Surakarta - Gunawan Gunawan; Anisyah Dewi Syah Fitri (Poltekkes Kemenkes Surakarta, 2019)
Background: Hearing loss is the difficulty of someone to hear sounds from mild to severe degrees, so that they experience obstacles in understanding other people's speech through their own hearing or someone who has lost the ability to hear so that they cannot process language information through hearing with or without hearing aids (Travis, 1978).Based on the Results of Basic Health Research conducted by the Indonesian Ministry of Health in 2013 (Riskesdas 2013) presents significant information in terms of the prevalence of disability in children. The prevalence of blind people is 0.17%, speech impaired 0.14%, down syndrome 0.13%, physical impairment 0.08, hearing impaired 0.07% and disability caused by trauma and accidents 0.53%. In children aged 24 - 59 months found 0.14% of children who are speechless from the overall data of children with disabilities.Speech therapy to handle cases of hearing loss, with Speech Trainer aids, especially articulations.The main purpose of providing effective information and benefits of speech trainer aids for speech therapy cases of dysaudia aged 3-6 years specifically in the pronunciation of consonant / r / Late articulation.Providing information to the Speech Therapist, one of the procedures in the use of speech trainer therapy aids, especially in the case of dysaudia who do not use Google implants.Providing information and understanding to parents about the problem of a child's condition that does not use sophisticated Google implants, can be treated with speech trainer. Because Koglea implants are expensive. Methods: This research uses survey method, aims to find information that will be used to solve problems and not to test hypotheses.The instruments in this study were consonants / r / followed by vocal sounds [/ a /, / i /, / u / e /, / e / and / o /] the final position in the form of words as follows: Snake, Comb, Egg , Suitcase, Bucket, Tail. With the help of pictures. and Therapeutic Tools used in intervening in Children, namely: Speech Trainer and Consonant / r / Articulation Card and Mirror. Results: Based on the results of this study, it can be concluded that from the study land surveyed as many as 4 (four) children with hearing loss in YPAC. Conclusion: Speech Trainer did not show any influence at the time of T1 to T4, there was an influence at the time of T5 that is indicated in the word Comb there were 3 subjects (75.0%), eggs had 3 subjects (75.0%), Buckets had 1 Subject ( 25.0%), and tails there were 2 subjects (50.0%), whereas in the word snake, and luggage did not show any successful pronunciation.The effectiveness of using Speech Trainer lies in the pronunciation of the consonant / r / on the word comb and egg on T5 (p = 0.010).